Open Access Musicology Volume Two - Epstein, Louis; Barolsky, Daniel (Lever Press, 2022)
Open Access Musicology (OAM) publishes peer-reviewed, scholarly essays primarily intended to serve students and teachers of music history, ethno/musicology, and music studies. The constantly evolving collection ensures that recent research and scholarship inspires classroom practice. OAM essays provide diverse and methodologically transparent models for student research, and they introduce different modes of inquiry to inspire classroom discussion and varied assignments. Addressing a range of histories, methods, voices, and sounds, OAM embraces changes and tensions in the field to help students understand music scholarship. In service of our student- and access-centered mission, Open Access Musicology is a free collection of essays, written in an engaging style and with a focus on modes of inquiry rather than coverage of content. Our authors draw from their experience as scholars but also as teachers. They not only make arguments, but also describe why they became musicologists in the first place and explain how their individual paths led to the topics they explore. Like most scholarly literature, the essays have all been reviewed by experts in the field. Unlike most scholarly literature, the essays have also been reviewed by students at a variety of institutions for clarity and relevance. These essays are intended for undergraduates, graduate students, and interested readers without any particular expertise. They can be incorporated into courses on a range of topics as standalone readings, used to supplement textbooks, or read with an eye to new scholarly insights. The topics introduce and explore a variety of subjects, practices, and methods but, above all, seek to stimulate classroom discussion on music history's relevance to performers, listeners, and citizens. Open Access Musicology will never pretend to present complete histories, cover all elements of a subject, or satisfy the agenda of every reader. Rather, each essay provides an opening to further contemplation and study. We invite readers to follow the thematic links between essays, pursue notes or other online resources provided by authors, or simply repurpose the essay's questions into new and exciting forms of research and creativity. Volume 2 of OAM expands the disciplinary, topical, and geographical ranges of our endeavor, with essays that rely on ethnographic and music theoretical methods as well as historical ones. The essays in this volume touch on music from Europe, South America, and Asia, spanning the 16th century to the present. Throughout, the contributing authors situate music in political, religious, racial, economic, and other cultural and disciplinary contexts. This volume therefore expands what scholars generally mean when they refer to "musicology" and "music," always with an eye toward relevance and accessibility.